2020
DOI: 10.1371/journal.pone.0243329
|View full text |Cite
|
Sign up to set email alerts
|

Views of patients suffering from Failed Back Surgery Syndrome on their health and their ability to adapt to daily life and self-management: A qualitative exploration

Abstract: Background The clinical outcomes of Spinal Cord Stimulation (SCS) therapy in patients with a Failed Back Surgery Syndrome (FBSS) is mostly done by standardized pain and quality of life measurements instruments and hardly account for personal feelings and needs as a basis for a patient-centred approach and shared decision making. Objectives The objective of this study is to explore perspectives on personal health and quality of life (QoL) in FBSS patients concerning their physical-, psychological and spiritua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, eight articles reported that the dimensions of PH were part of their qualitative research methods, either during data collection [ 34 , 37 , 52 , 59 , 71 ] or as a framework during data analysis to organise themes based on the various dimensions [ 43 , 52 , 67 , 69 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, eight articles reported that the dimensions of PH were part of their qualitative research methods, either during data collection [ 34 , 37 , 52 , 59 , 71 ] or as a framework during data analysis to organise themes based on the various dimensions [ 43 , 52 , 67 , 69 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36] In this field of research on suffering, several studies have used a qualitative design when aiming to understand and explain this phenomenon. [37][38][39] The study was approved by the research ethics committee of the Centre intégré universitaire de santé et de services sociaux du Centre-Sud de l'Île-de Montréal (Certificate # . All participants signed a consent form stating that their participation was voluntary.…”
Section: Methodsmentioning
confidence: 99%
“…The first section included questions based on the six dimensions of health according to the Machteld Huber model: bodily functions, mental well-being, meaningfulness, quality of life, participation, and daily functioning. [37][38][39] These questions delineated how pain affects a patient's life within the context of the six dimensions of health. The second part focused on the experiences of participants with the MDC and ideally led to a proposal of the participant to optimize CPP syndrome care.…”
Section: Data Collectionmentioning
confidence: 99%